Comparison of Multipath Protocol Improvements in SMMSN-AOMDV and MAN-AOMDV for Stable Node Selection in Ad Hoc Networks - Shian Safar SULAIMAN; Saad Sulaiman NAIF; Barzan Abdulazeez IDREES; Abdulraheem Jamil AHMED (Revista Română de Informatică și Automatică, 2025)
The future of the wireless networks holds a significant promise, particularly in the domain of the Mobile Ad hoc NETworks (MANETs), which continue to attract a growing academic interest. As MANET usage expands across diverse applications and user demands increase, an enhanced performance and reliability have become critical. Ensuring the Quality of Service (QoS) is essential for effective communication, with load balancing in routing protocols playing a vital role in optimizing the resource management and improving the overall network performance. In this study, two enhanced multipath routing protocols are proposed ‒ SMMSN-AOMDV (Stable Multi-path Selection with More Stable Nodes in AOMDV) and MAN-AOMDV (Multi-path Routing with Available Nodes in AOMDV)—specifically designed to improve route stability and load distribution in MANETs. The approach introduces a novel load balancing mechanism within the AOMDV protocol by selecting the paths based on node-level parameters and dynamically distributing traffic across less congested nodes during data transmission. The proposed protocols are implemented and evaluated using NS2 (Network Simulator 2). The simulation results demonstrate that the enhanced protocols significantly improve the key performance metrics, including the packet delivery ratio, throughput, and end-to-end delay.